Delivering quality service through innovation of existing health clinics for sustainability: a theoretical initiative through architectural design proposal - Mohd Nawawi, Norwina; Aripin, Srazali; Yun, Hasnah; Alwi, Nadiah; Wan Nor, Wan Fatihah Maisarah; Zakariya, Farah Atiqah (2019)
Improvement in the Quality of Health of Malaysians is part of 2nd Strategic Thrust of the Midterm Review 2016-2020 by the government focusing on “Improving Wellbeing for All”, by 2020. The primary health sector, as the safety net for the healthy nation, remain the focal point for all to access healthcare. With over 2881 number of health clinics all around the country, of various degree of building age, sizes and designs, the demand for quality care require a review of the facilities and its’ ability to improve while functioning. Existing clinics are the gems for the local populace. Replacing them to faraway places is not an idea of accessibility and place continuity. This paper thus aims at addressing the meaning of quality service from architectural facility expectation in the remake of selected aged facilities to meet prevailing standards and reasonable expectations. Through qualitative research by selected case studies of aged facilities and literature review, including new design briefs of government health clinics, the findings, through observation and interview, a scenario for the remake will be churned. Architectural expressions of the remake as design proposal will be recommended to the Ministry of Health Malaysia as a spur towards more design review of other clinics as proactive measure from public works department, the university or the NGO, who cares